The Onset of Miliary Tuberculosis Presenting after an Episode of Angina, Palpitations and Cardiac Stent Placement - Suha Moten; Alyssa Panganiban; Anis Abdul Rauf; Jaqueline Walker (Archives of Pulmonology and Respiratory Care - Peertechz Publications, 2020)
The novel Coronavirus of 2019 (COVID-19) has dramatically reminded the world of the importance of noting pertinent travel history. Increasing global travel and immigration require physicians to include travel history when considering their differential diagnoses. In this report, we present a 75-year-old male diagnosed with Miliary Tuberculosis (TB) after returning from vacation in Mexico. During his vacation, he had symptoms attributed to unstable angina and underwent a cardiac catheterization requiring the placement of a drug eluting stent. This case report discusses angina as a possible presenting symptom of Miliary TB. Cardiac arrhythmia is a known risk of TB and it should be suspected in patients with arrhythmias with a recent travel history, as it is estimated that 1% of all cases of TB have cardiac involvement [1]. Ultimately, with the aging of the population and our increasing mobile population, Miliary TB must be considered more frequently in our differentials in the developed world due to the aging of the population and increased ease of international travel.